2014
DOI: 10.1016/j.ntt.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and regulation of motor responses in cocaine-exposed infants

Abstract: Effects of prenatal exposure to cocaine on the reactivity and regulation of the motor system of 825 four-month-old infants enrolled in the Maternal Lifestyle Study were examined. Videotaped assessments of 338 cocaine-exposed (CE) infants and 487 non-exposed comparison infants were coded by examiners masked to exposure status. Exposure status was determined by meconium assay and maternal self-report of prenatal cocaine use. Infants were presented with a series of 17 visual, auditory and tactile stimuli for 30-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…This finding is consistent with behavioral reports demonstrating motor function abnormalities within a broad spectrum of prenatal drug exposures (Connor et al, 2006; Fallone et al, 2014; Kronstadt, 1991). …”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with behavioral reports demonstrating motor function abnormalities within a broad spectrum of prenatal drug exposures (Connor et al, 2006; Fallone et al, 2014; Kronstadt, 1991). …”
Section: Discussionsupporting
confidence: 92%
“…Singer et al (2002) reported that this effect was not obvious at 2 years. In their recent study, Fallone et al (2014) reported that COC-exposed infants did not have a highly active motor system. However, these infants exhibited increased movement activity for a longer period of time after the initial stimulation (Fallone et al, 2014).…”
Section: Motor Skillsmentioning
confidence: 99%
“…In their recent study, Fallone et al (2014) reported that COC-exposed infants did not have a highly active motor system. However, these infants exhibited increased movement activity for a longer period of time after the initial stimulation (Fallone et al, 2014). Miller-Loncar et al (2005) attempted to evaluate the potential predictors of motor development among children prenatally exposed to COC.…”
Section: Motor Skillsmentioning
confidence: 99%